Molecular Genetics and Pathogenesis of the Floating Harbor Syndrome: Case Report of Long-Term Growth Hormone Treatment and a Literature Review - Turkunova, Mariia E.; Barbitoff, Yury A.; Serebryakova, Elena A.; Polev, Dmitrii E.; Berseneva, Olga S.; Bashnina, Elena B.; Baranov, Vladislav S.; Glotov, Oleg S.; Glotov, Andrey S. (Frontiers in Genetics, 2022)
Introduction. Floating Harbor syndrome (FHS) is an extremely rare disorder, with slightly more than a hundred cases reported worldwide. FHS is caused by heterozygous mutations in the SRCAP gene; however, little is known about the pathogenesis of FHS or the effectiveness of its treatment. Methods. Whole-exome sequencing (WES) was performed for the definitive molecular diagnosis of the disease. Identified variants were validated using Sanger sequencing. In addition, systematic literature and public data on genetic variation in SRCAP and the effects of growth hormone (GH) treatment was conducted. Results. We herein report the first case of FHS in the Russian Federation. The male proband presented with most of the typical phenotypic features of FHS, including short stature, skeletal and facial features, delayed growth and bone age, high pitched voice, and intellectual impairment. The proband also had partial growth hormone deficiency. We report the history of treatment of the proband with GH, which resulted in modest improvement in growth prior to puberty. WES revealed a pathogenic c.7466C>G (p.Ser2489*) mutation in the last exon of the FHS-linked SRCAP gene. A systematic literature review and analysis of available genetic variation datasets highlighted an unusual distribution of pathogenic variants in SRCAP and confirmed the lack of pathogenicity for variants outside of exons 33 and 34. Finally, we suggested a new model of FHS pathogenesis which provides possible basis for the dominant negative nature of FHS-causing mutations and explains limited effects of GH treatment in FHS. Conclusions. Our findings expand the number of reported FHS cases and provide new insights into disease genetics and the efficiency of GH therapy for FHS patients.